History of journalism of Russian South Region (Akhmadulin E.V, Stanko A.I. Regional printing of Don and North Caucasus XIX - beginning XX centuries. Rostov-on-Don: Southern Federal University press, 2014. 372 p.) (Proceedings of Southern Federal University. Philology, 2016)
Abramovich T.S. REVIEWS